Német nemzetiségi oktatás – kisebbségpolitika az Osztrák-Magyar Monarchia felbomlásától 1945-ig - Dávid, Gabriella (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2018)
Besides the military defeat, the fall of the Austro-Hungarian Empire was also due to the nationalist movements. In October 1918 Mihály Károlyi formed the Hungarian government and in November the new Ministry of Religion and Public Education launched its programme of how to make profound changes in the public education. Education became compulsory till the age of 14 and education was free. Gradual consolidation in the early 1920s was facilitated by vicomt Kunó Klebelsberg, the head of the national cultural policy and public education. In his opinion, culture was the major motive for further developement. In areas, inhabited by minorities, public schools were opened where education was provided in the language of the minority. Public elementary schools for minorities were provided in detail by Klebelsberg so that the schools would be suitable for the conditions of the dispersed minority.